Sports and exercise nutrition - Katch, Frank I.; McArdle, William D.;Katch, Victor L. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2013)
Sports and Exercise Nutrition, Fourth Edition, offers a one-semester introduction to the basics of nutrition and the effect of nutrition decisions on performance. It focuses on the integration of nutrition and exercise and its impact on optimal exercise performance and training responsiveness. As you progress through the text, you'll learn about nutrient digestion and absorption and how nutrition affects energy and metabolism. Further sections expand on this foundational content to highlight using nutrition to affect performance in different environments, the purpose of supplements and nutritional aids, and how nutrition affects body composition and weight control. Moreover, you'll discover how to make prudent decisions in the nutrition-fitness marketplace. This Fourth Edition incorporates new content and features while maintaining its hallmark writing style. An extensively revised art program provides new and updated graphics to help explain and expand on the content in a unique way. Plus, each section has undergone a major revision, offering you coverage of new and emerging topics in nutrition and exercise as well as the latest research findings.
The macronutrients -- The micronutrients and water -- Digestion and absorption of the food nutrients -- Nutrient role in bioenergetics -- Macronutrient metabolism in exercise and training -- Measurement of energy in food and during physical activity -- Nutritional recommendations for the physically active person -- Nutritional considerations for intense training and sports competition -- Making wise choices in the nutrition marketplace -- Exercise, thermoregulation, fluid balance, and rehydration -- Pharmacologic and chemical ergogenic aids evaluated -- Nutritional ergogenic aids evaluated -- Body composition assessment and sport-specific observations -- Energy balance, exercise, and weight control -- Disordered eating.
Includes index.
Keywords: SPORTS